PPARg mRNA in the adult mouse hypothalamus: distribution and regulation in response to dietary challenges - Yang eLiu; Ying eHuang; Syann eLee; Angie L Bookout; Carlos M Castorena; Wua eHu; Laurent eGautron (Frontiers Media S.A., 2015)
Peroxisome proliferator-activated receptor gamma (PPARg) is a ligand-activated transcription factor that was originally identified as a regulator of peroxisome proliferation and adipocyte differentiation. Emerging evidence suggests that functional PPARg signaling also occurs within the hypothalamus. However, the exact distribution and identities of PPARg-expressing hypothalamic cells remains under debate. The present study systematically mapped PPARg mRNA expression in the adult mouse brain using in situ hybridization histochemistry. PPARg mRNA was found to be expressed at high levels outside the hypothalamus including the neocortex, the olfactory bulb, the organ of the vasculosum of the lamina terminalis, and the subfornical organ. Within the hypothalamus, PPARg was present at moderate levels in the suprachiasmatic nucleus and the ependymal of the 3rd ventricle. In all examined feeding-related hypothalamic nuclei, PPARg was expressed at very low levels that were close to the limit of detection. Using qPCR techniques, we demonstrated that PPARg mRNA expression was upregulated in the suprachiasmatic nucleus in response to fasting. Double in situ hybridization further demonstrated that PPARg was primarily expressed in neurons. Collectively, our observations provide a comprehensive map of PPARg distribution and regulation in the intact adult mouse hypothalamus.